OFFSPRING BIRTH WEIGHT AND MATERNAL FASTING LIPIDS IN WOMEN SCREENED FOR GESTATIONAL DIABETES MELLITUS - Dr. Janaki Menon C.M; Dr. Nagarathna G; Dr. Sudeep K. (Medico Research Chronicles, 2018)
Introduction: The most common neonatal complication of gestational DM is macrosomia. During early pregnancy, an accumulation of maternal fat depots occurs followed by increased adipose tissue lipolysis and subsequent hyperlipidemia which mainly corresponds to increased triglycerides in all circulating lipoproteins. In GDM women the enhanced insulin resistance and altered estrogen-progesterone ratio are responsible for the reported wide range of dyslipidemic conditions1. Association of high maternal glucose levels and fetus macrosomia have been documented. The prospective Amsterdam Born children and development cohort study, reported that high maternal TG levels in early pregnancy were associated with higher Birth weights and subsequently a higher occurrence of LGA births, whereas low TG levels were associated with accelerated postnatal growth2. Total cholesterol, HDL and lipoprotein concentrations are not significantly different between GDM patients and control subjects3. Materials and Methods: It is a prospective observational study done on patients coming to the department of OBG, Father Mullers Hospital, Mangalore for antenatal checkup over the period of one year and nine months. All Antenatal mothers are advised to undergo OGCT test as part of universal screening for GDM according to their convenience. Minimum of 100 Patients with positive OGCT (> 140mg/dl) were selected. Detailed clinical evaluation including relevant history and physical examination was undertaken. They are asked to undergo OGTT test. Results: Among the total of hundred GCT positive patients studied, 41 patients were GTT positive and 59 were GTT negative. Elevated triglycerides were found in 31(75%) of GTT positive patients. Elevated serum cholesterol levels were seen in 21(51.21%) of GDM mothers. Forty-one (69%) patients in the normal GTT group had elevated triglycerides and 31(52%) among the normal GTT group had elevated cholesterol. Among the 100 patients studied, there were 25 babies with birth weight more than 3.5 kg. Discussion and Conclusion: Various studies have been conducted in different parts of the world to correlate between maternal glucose levels and macrosomia as well as lipid alterations with fetal weight changes in normoglycemic as well as diabetic patients. Our study was also aimed at finding whether any relationship existed between the development of macrosomia in diabetic or nondiabetic patients and relationship with maternal fasting lipids, mainly serum triglycerides. Our study shows elevated triglycerides and cholesterol both in gestational diabetic patients as well as nondiabetic controls. Conclusion: Our study did not find any positive correlation between elevated triglycerides and GDM as well as between elevated total serum cholesterol and GDM. Elevated birthweight more than 3500 g also was not significantly found to be associated with either elevated serum triglyceride levels or serum cholesterol levels.